Understanding how finance can better serve the economy, society and the environment.
During its final conference in Brussels from 27 to 28 September, the FESSUD project brought together leading academics, economists and financial experts to disseminate its key results and discuss how Europe's financial system can be better structured to serve economic, societal and environmental needs.